Preparation of manganese-cobalt spinel catalyst and application of manganese-cobalt spinel catalyst in room-temperature catalytic ozonation of VOCs
By developing bimetal oxide manganese cobalt spinel catalyst, using in-situ impregnation water-thermal growth and high-temperature calcination technology, the problem of insufficient activity of existing catalysts at room temperature is solved, and efficient catalytic decomposition and ozone removal of various VOCs are achieved.
Patent Information
- Application Number
- CN202411707273.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-11-27
AI Technical Summary
The existing catalysts have insufficient activity in room temperature catalyzed ozonated VOCs and cannot meet the actual application needs of the industry.
The in-situ impregnation water-thermal growth technology was used to develop a bimetal oxide manganese cobalt spinel monolithic catalyst, and the activity of the catalyst was improved by high-temperature calcination.
At room temperature, VOCs such as toluene, methanol, and propylene have 100% catalytic decomposition activity, and at 53°C, the catalyst has a higher removal rate of ozone at room temperature.
Smart Images

Figure CN119608177A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of material technology, and in particular relates to the preparation of a manganese-cobalt spinel catalyst and its application in catalytic ozonation of VOCs at room temperature. Background Art
[0002] Volatile organic compounds (VOCs) mainly come from pollutant emissions from fixed and mobile sources. Fixed sources mainly include industrial emissions such as coal-fired power plants and chemical plants, while mobile sources mainly come from motor vehicle exhaust. The emission of volatile organic compounds is one of the main factors causing air pollution, which is harmful to human health and the ecological environment. Therefore, it is very important to find an effective method to remove VOCs. One of the mainstream methods currently used to remove VOCs is catalytic combustion, which can effectively remove VOCs at high temperatures (500-800°C), but its energy consumption is relatively high and its industrial application is not economical. Catalytic ozonation technology is a new room temperature process technology that decomposes ozone into active oxygen species with higher oxidation ability on the catalyst surface to efficiently degrade pollutants. With the assistance of a suitable catalyst, ozone can be decomposed to produce active oxygen free radicals at room temperature and pressure, greatly reducing the operating cost and safety hazards of industrial VOCs waste gas treatment. At the same time, it has three advantages: high activity at room temperature, high stability and economic feasibility. However, the development of existing catalysts, especially industrial environmental protection catalysts, is still mainly centered around catalytic oxidation technology. There is currently little research on industrial catalysts for room temperature catalytic ozone oxidation technology, and there is basically no industrial application. This is mainly due to the poor activity of single metal oxides in room temperature catalytic ozone oxidation catalysts, which cannot meet the actual industrial application requirements. Summary of the invention
[0003] Based on this, the present invention proposes a preparation method of a manganese-cobalt spinel catalyst and its application in catalytic ozonation of VOCs at room temperature. Mainly aimed at the problem of insufficient active sites for catalytic ozonation using a single metal oxide catalyst in the prior art, the in-situ impregnation hydrothermal growth technology is innovatively used to develop a bimetallic oxide manganese-cobalt spinel monolithic catalyst to meet the actual needs of the industry.
[0004] To achieve the above object, the present invention provides the following technical solutions:
[0005] A method for preparing a manganese-cobalt spinel catalyst comprises the following steps:
[0006] 1) adding manganese salt and cobalt salt into water and dissolving them by ultrasonic, immersing the honeycomb ceramic substrate in the obtained solution, and taking out the treated honeycomb ceramic substrate after the solution turns into light purple; repeating the immersion three times;
[0007] 2) drying and calcining the honeycomb ceramic substrate after the impregnation treatment;
[0008] 3) The calcined honeycomb ceramic substrate is immersed in an acetic acid solution, and then the excess solution in the pores is blown away, and then immersed in a lanthanum salt solution, and then the excess solution in the pores is blown away after being taken out, and then dried, and the temperature is raised and calcined again to obtain a manganese cobalt spinel catalyst.
[0009] Furthermore, in step 1), the parameters of the immersion are: temperature 85-95° C., time 4-4.5 hours.
[0010] Furthermore, in step 1), the molar ratio of the manganese salt to the cobalt salt is 7:10.
[0011] Furthermore, the manganese salt is potassium permanganate, the cobalt salt is cobalt nitrate hexahydrate, and the lanthanum salt is lanthanum nitrate hexahydrate.
[0012] Further, in step 2) and step 3),
[0013] The drying parameters are: temperature 150°C, time 6 hours; and / or
[0014] The calcination parameters are: temperature 500° C., time 2.5 hours, heating rate 10° C. / min.
[0015] Further, in step 3),
[0016] The concentration of the acetic acid solution is 0.1-0.2 mol / L; and / or
[0017] The soaking parameters are: time 1-2 hours; and / or
[0018] The concentration of the lanthanum salt solution is 0.15-0.2 mol / L; and / or
[0019] The parameters of the immersion are: time 10-20 minutes.
[0020] The present invention also provides a manganese-cobalt spinel catalyst prepared by the above preparation method.
[0021] The present invention also provides an application of the manganese-cobalt spinel catalyst in catalytic ozonation of VOCs.
[0022] Catalytic ozonation technology is a new process that decomposes ozone into active oxygen species with higher oxidation ability on the catalyst surface to efficiently degrade pollutants. With the assistance of the catalyst prepared by the present invention, ozone can be decomposed to produce active oxygen free radicals at room temperature and pressure, greatly reducing the operating cost and safety hazards of VOCs waste gas treatment equipment, and has the advantages of low temperature, high activity and economic feasibility.
[0023] Compared with the prior art, the present invention has the following advantages and technical effects:
[0024] The present invention efficiently synthesizes the manganese-cobalt spinel catalyst through a simple in-situ impregnation hydrothermal growth-high temperature calcination method. The method is simple and efficient and can be applied to industrial large-scale batch preparation of catalysts in the future.
[0025] Under catalytic ozonation conditions, the manganese-cobalt spinel catalyst prepared by the method of the present invention has 100% catalytic decomposition activity for toluene, methanol and propylene at room temperature, and has 100% catalytic decomposition activity for ethyl acetate at 53°C. In addition, the catalyst also has a high removal rate for ozone at room temperature. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:
[0027] Figure 1 The picture and scanning electron microscope image of the manganese-cobalt spinel monolithic catalyst prepared in Example 1 of the present invention;
[0028] Figure 2 This is the XRD pattern of the manganese-cobalt spinel monolithic catalyst prepared in Example 1 of the present invention;
[0029] Figure 3 The room temperature catalytic ozonation decomposition activity curve of toluene by the manganese-cobalt spinel monolithic catalyst prepared in Example 1 of the present invention;
[0030] Figure 4 The room temperature catalytic ozonation decomposition activity curve of toluene by the manganese-cobalt spinel monolithic catalyst prepared in Example 1, Comparative Example 1 and Comparative Example 2 of the present invention;
[0031] Figure 5 The room temperature catalytic ozonation decomposition activity curve of toluene by the manganese-cobalt spinel monolithic catalyst prepared in Example 1, Comparative Example 3 and Comparative Example 4 of the present invention;
[0032] Figure 6 This is the room temperature catalytic ozonation decomposition activity curve of methanol by the manganese-cobalt spinel monolithic catalyst prepared in Example 1 of the present invention;
[0033] Figure 7 This is the room temperature catalytic ozonation decomposition activity curve of propylene by the manganese-cobalt spinel monolithic catalyst prepared in Example 1 of the present invention;
[0034] Figure 8 The activity curve of the manganese-cobalt spinel monolithic catalyst prepared in Example 1 of the present invention for catalytic ozonation decomposition of ethyl acetate;
[0035] Fig. 9The activity curve of the manganese-cobalt spinel monolithic catalyst prepared in Example 1 of the present invention for catalytic ozonation decomposition of methane;
[0036] Fig.10 The catalytic ozonation decomposition activity curve of the manganese-cobalt spinel monolithic catalyst prepared in Example 1 of the present invention for mixed gas;
[0037] Fig.11 The decomposition activity curve of the manganese-cobalt spinel monolithic catalyst prepared in Example 1 of the present invention to ozone at room temperature and different humidity;
[0038] Fig.12 This is the room temperature catalytic ozonolysis activity curve of toluene by the catalyst of Comparative Example 5 of the present invention. DETAILED DESCRIPTION
[0039] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0040] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0041] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0042] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0043] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0044] The present invention provides a method for preparing a manganese-cobalt spinel catalyst, comprising the following steps:
[0045] 1) adding soluble manganese salt and soluble cobalt salt into water and dissolving them by ultrasonication, then placing them in a water tank with a honeycomb ceramic substrate and stirring them at a constant temperature, and taking out the treated honeycomb ceramic substrate after the solution turns into light purple; repeating the immersion three times to achieve the purpose of multiple in-situ hydrothermal growth under constant temperature reaction conditions;
[0046] 2) drying the honeycomb ceramic substrate grown multiple times by in-situ hydrothermal treatment, and then placing it in a furnace for high-temperature calcination;
[0047] 3) The calcined honeycomb ceramic substrate is immersed in an acetic acid solution, and then the excess solution in the pores is blown away, and then it is taken out and immersed in a soluble lanthanum salt solution, and then the excess solution in the pores is blown away again, and then it is dried and calcined again to obtain a manganese cobalt spinel catalyst.
[0048] In a preferred embodiment of the present invention, the repeated impregnation means that each time the manganese salt and the cobalt salt are added to water and ultrasonically dissolved to prepare a solution, and then the honeycomb ceramic substrate treated by the previous impregnation treatment is placed in a new solution for a new round of impregnation treatment. Specifically:
[0049] Firstly, manganese salt and cobalt salt are added into water and ultrasonically dissolved, and the honeycomb ceramic substrate is immersed in the obtained solution. After the solution turns into light purple, the honeycomb ceramic substrate treated for the first time is taken out;
[0050] A second time, manganese salt and cobalt salt are added into water and ultrasonically dissolved, and the honeycomb ceramic substrate treated for the first time is immersed in the obtained solution, and after the solution turns into light purple, the honeycomb ceramic substrate treated for the second time is taken out;
[0051] The manganese salt and the cobalt salt are added into water for the third time and ultrasonically dissolved, and the honeycomb ceramic substrate treated for the second time is immersed in the obtained solution. After the solution turns into light purple, the honeycomb ceramic substrate treated for the third time is taken out.
[0052] In the three processes, the preparation method and dosage of manganese salt and cobalt salt were the same.
[0053] The reason why the solution turns lavender is that the aqueous solution of potassium permanganate is purple and the aqueous solution of cobalt nitrate is pink. When the two are mixed and added into water for ultrasonic dissolution, the resulting solution is purplish red. When the honeycomb ceramic carrier is immersed in the purplish red solution for reaction, the potassium permanganate is reduced and the cobalt ions interact with the substrate material, resulting in a decrease in the concentration of free cobalt ions in the solution, thereby making the solution lighter in color. That is, the immersion process consumes potassium permanganate and cobalt nitrate at the same time, so the solution color becomes lighter.
[0054] In a preferred embodiment of the present invention, in step 1), the parameters of the three dippings are: temperature 85-95°C, time 4-4.5 hours. Exemplarily, in the following embodiments of the present invention, the three dipping temperatures are all taken as 86°C and 4.5 hours for dipping to verify the effect.
[0055] In the following preferred embodiment of the present invention, in step 1), the molar ratio of the manganese salt to the cobalt salt is 7:10.
[0056] In a preferred embodiment of the present invention below, manganese salt, cobalt salt and lanthanum salt are all hydrates, such as potassium permanganate hydrate, cobalt nitrate hydrate, lanthanum nitrate hydrate. Exemplarily, in the following embodiments of the present invention, potassium permanganate, cobalt nitrate hexahydrate and lanthanum nitrate hexahydrate are used as examples to verify the effect.
[0057] In a preferred embodiment of the present invention, in step 2) and step 3),
[0058] The drying parameters are: temperature 150°C, time 6 hours;
[0059] The calcination parameters are: temperature 500° C., time 2.5 hours, heating rate 10° C. / min.
[0060] In a preferred embodiment of the present invention, in step 3),
[0061] The concentration of the acetic acid solution is 0.1-0.2 mol / L. For example, in the following embodiments of the present invention, the concentration of the acetic acid solution is 0.1 mol / L as an example for effect verification.
[0062] The soaking parameters are: time 1-2 hours; exemplary, in the following embodiments of the present invention, the soaking time is 1 hour as an example for effect verification;
[0063] The concentration of the lanthanum salt solution is 0.15-0.2 mol / L; illustratively, in the following embodiments of the present invention, the concentration of the lanthanum salt solution is 0.15 mol / L as an example for effect verification;
[0064] The parameters of the immersion are: time 10-20 minutes. For example, in the following embodiments of the present invention, the effect is verified by taking the immersion time of 10 minutes as an example.
[0065] The manganese-cobalt spinel catalyst is prepared by the above preparation method.
[0066] The above-mentioned manganese cobalt spinel catalyst is used in the catalytic ozonation of VOCs, wherein the VOCs include: toluene, methanol, propylene, ethyl acetate, methane, ozone and a mixed gas composed of several gases. During the application process, the test conditions are: the test gas flow rate is 100mL / min, the oxygen flow rate is 0-30mL / min (such as 0mL / min or 30mL / min), the ozone concentration is 17-700ppm (such as 17ppm or 700ppm), the N2 as the balance gas flow rate is 36.7-50mL / min (such as 36.7mL / min or 50mL / min), the test gas concentration is 100ppm, the test gas flow rate is 20-33.3mL / min (such as 20mL / min or 33.3mL / min), and the volume space velocity is 600-18950h -1 (e.g. 600h -1 , 2400h -1 or 18950h -1 ), the test temperature is room temperature-400°C (such as room temperature, 53°C or 400°C).
[0067] The "room temperature" mentioned in the present invention refers to 25±2°C unless otherwise specified.
[0068] The raw materials used in the present invention are all purchased from the market.
[0069] The technical solution of the present invention is further illustrated by the following embodiments.
[0070] Example 1
[0071] Preparation of a manganese-cobalt spinel catalyst:
[0072] Potassium permanganate and cobalt nitrate hexahydrate were mixed in a molar ratio of 7:10 and added to water for ultrasonic stirring and dissolution (the concentration of potassium permanganate in the obtained solution was 0.032 mol / L, and the concentration of cobalt nitrate hexahydrate was 0.048 mol / L); the fully mixed solution was added to a water tank with a honeycomb ceramic substrate and stirred at 86°C for 4.5 hours. After the solution turned into light purple, the solution was discharged from the liquid discharge port, the solution was prepared 3 times, and hydrothermal growth was repeated 3 times at 86°C for 4.5 hours; after the in-situ hydrothermal growth reaction was completed, the reaction solution was discharged, the solution in the pores was blown out, and the substrate was placed in an oven for 1 hour. The catalyst was dried at 50°C for 6 hours, and then calcined at 500°C for 2.5 hours at a heating rate of 10°C / min; the monolithic catalyst obtained above was immersed in a 0.1mol / L acetic acid solution for 60 minutes, and then the excess solution in the pores was blown away. After being taken out, it was immersed in a 0.15mol / L lanthanum nitrate hexahydrate solution for 10 minutes, and then the excess solution in the pores was blown away, and it was placed in an oven and dried at 150°C for 6 hours; finally, the monolithic catalyst was calcined at a constant temperature of 500°C for 2.5 hours at a heating rate of 10°C / min to obtain a manganese cobalt spinel monolithic stone catalyst (MC-500°C).
[0073] Comparative Example 1
[0074] The same as Example 1, except that the calcination temperature is adjusted from 500°C to 600°C to obtain a manganese-cobalt spinel monolithic catalyst (MC-600°C).
[0075] Comparative Example 2
[0076] The same as Example 1, except that the calcination temperature is adjusted from 500°C to 700°C to obtain a manganese-cobalt spinel monolithic catalyst (MC-700°C).
[0077] Comparative Example 3
[0078] The same as Example 1, except that potassium permanganate and cobalt nitrate hexahydrate are mixed in a molar ratio of 7:10 to adjust to: potassium permanganate and cobalt nitrate hexahydrate are mixed in a molar ratio of 3:10 to obtain a manganese-cobalt spinel monolithic catalyst.
[0079] Comparative Example 4
[0080] The same as Example 1, except that potassium permanganate and cobalt nitrate hexahydrate are mixed in a molar ratio of 7:10 and adjusted to potassium permanganate and cobalt nitrate hexahydrate in a molar ratio of 5:10 to obtain a manganese-cobalt spinel monolithic catalyst.
[0081] Comparative Example 5
[0082] Commercially available manganese oxide (MnO) and manganese dioxide (MnO2) catalysts were purchased from Aladdin (CAS: 1344-43-0) and Xianfeng Nano (CAS: 1313-13-9), respectively.
[0083] For the prepared manganese-cobalt spinel catalyst, the following Figure 1-2 The catalyst structure and morphology are characterized. Figure 1 The scanning electron microscope image shows that the prepared manganese-cobalt spinel monolithic catalyst has no clear morphology, and its surface elements are evenly distributed. Figure 2 From the XRD diagram, it can be seen that the characteristic peaks of Mn and Co metals do not appear in the manganese-cobalt spinel catalyst, indicating that the metallic manganese in the catalyst is highly dispersed or the content is lower than the detection limit, or the obtained metal oxide is calcined at a low temperature and it is difficult to form a good crystal structure.
[0084] Application Example 1
[0085] The manganese-cobalt spinel catalyst prepared in Example 1 was used to catalyze the ozonation of VOCs at room temperature. Figure 3 The room temperature catalytic ozonation decomposition activity of toluene over manganese cobalt spinel catalyst was tested. The test conditions were as follows: the test gas was toluene, the total gas flow rate was controlled to be 100 mL / min, of which the oxygen flow rate was 30 mL / min, the ozone concentration was 700 ppm, the N2 balance gas flow rate was 36.7 mL / min, the toluene concentration was 100 ppm (the original toluene concentration in the gas cylinder was 500 ppm), the toluene flow rate was 33.3 mL / min, and the volume space velocity was 2400 h -1 The toluene concentration in the tail gas is detected and analyzed by gas chromatography, and the ozone concentration is detected by an ozone detector. Figure 3 It can be seen from the catalyst activity curve that the catalyst exhibits 100% toluene catalytic ozonation activity at room temperature, and the catalyst activity does not decrease after 20 hours, and can still maintain 100% toluene decomposition activity, showing good catalytic stability.
[0086] Application Example 2
[0087] Figure 4 The room temperature catalytic ozonation decomposition activity of toluene of the manganese-cobalt spinel catalyst prepared in Example 1, Comparative Example 1 and Comparative Example 2 was tested. The test conditions were as follows: the test gas was toluene, the total gas flow rate was controlled to be 100 mL / min, the oxygen flow rate was 30 mL / min, the ozone concentration was 700 ppm, the N2 balance gas flow rate was 36.7 mL / min, the toluene concentration was 100 ppm (the original toluene concentration in the gas cylinder was 300 ppm), the toluene flow rate was 33.3 mL / min, and the volume space velocity was 2400 h / min. -1 .from Figure 4 It can be seen from the catalyst activity curve that the manganese cobalt spinel catalyst (MC-600°C) prepared in Comparative Example 1 showed 100% toluene catalytic ozonation activity for only 2 hours, and the catalytic activity decreased significantly after 2 hours. The manganese cobalt spinel catalyst (MC-700°C) prepared in Comparative Example 2 was even worse, showing 100% toluene catalytic ozonation activity for less than 1 hour, and then the catalytic activity decreased significantly.
[0088] Application Example 3
[0089] Figure 5 The room temperature catalytic ozonation decomposition activity of toluene of the manganese-cobalt spinel catalyst prepared in Example 1, Comparative Example 3 and Comparative Example 4 was tested. The test conditions were as follows: the test gas was toluene, the total gas flow rate was controlled to be 100 mL / min, the oxygen flow rate was 30 mL / min, the ozone concentration was 700 ppm, the N2 balance gas flow rate was 36.7 mL / min, the toluene concentration was 100 ppm (the original toluene concentration in the gas cylinder was 300 ppm), the toluene flow rate was 33.3 mL / min, and the volume space velocity was 2400 h / min. -1 .from Figure 5 It can be seen from the catalyst activity curve that the manganese-cobalt spinel catalyst prepared in Comparative Example 3 showed that 90% of the toluene catalytic ozonation activity was only maintained for about 1 hour, and lost its catalytic activity after more than 1 hour. The manganese-cobalt spinel catalyst prepared in Comparative Example 4 was extremely unstable in its toluene catalytic ozonation activity and directly lost its activity after 4 hours of catalysis.
[0090] Application Example 4
[0091] Figure 6 The room temperature catalytic ozonation decomposition activity of methanol by the manganese-cobalt spinel catalyst prepared in Example 1 was tested. The test conditions were as follows: the test gas was methanol, the total gas flow rate was controlled to be 100 mL / min, the oxygen flow rate was 30 mL / min, the ozone concentration was 700 ppm, the N2 balance gas flow rate was 50 mL / min, the methanol concentration was 100 ppm (the original methanol concentration in the gas cylinder was 500 ppm), the gas flow rate was 20 mL / min, and the volume space velocity was 2400 h / min. -1 The methanol concentration in the tail gas is detected and analyzed by gas chromatography, and the ozone concentration is detected by an ozone detector. Figure 6 It can be seen from the catalyst activity curve that the manganese-cobalt spinel catalyst prepared in Example 1 exhibits 100% methanol catalytic ozonation activity at room temperature, and the catalyst activity does not decrease after 24 hours, and can still maintain 100% methanol decomposition activity, showing good stability.
[0092] Application Example 5
[0093] Figure 7 The room temperature catalytic ozonation decomposition activity of propylene by the manganese cobalt spinel catalyst prepared in Example 1 was tested. The test conditions were as follows: the test gas was propylene, the total gas flow rate was controlled to be 100 mL / min, the oxygen flow rate was 30 mL / min, the ozone concentration was 700 ppm, the N2 balance gas flow rate was 50 mL / min, the propylene concentration was 100 ppm (the original ethyl acetate concentration in the gas cylinder was 500 ppm), the gas flow rate was 20 mL / min, and the volume space velocity was 600 h / min. -1 . With a volume space velocity of 2400h -1 As a control group, the concentration of propylene in the tail gas was detected and analyzed by gas chromatography, and the concentration of ozone was detected by an ozone detector. Figure 7 The catalyst activity curve shows that at a volume space velocity of 600 h -1 The catalyst prepared in Example 1 exhibited 100% propylene catalytic ozonation activity at room temperature, and the catalyst activity did not decrease after 24 hours, and could still maintain 100% propylene decomposition activity, showing good stability. -1 When the catalyst prepared in Example 1 was kept at room temperature for 4 hours, the catalyst activity decreased significantly, and reached a stable state after 8 hours, maintaining about 40% of the propylene decomposition activity.
[0094] Application Example 6
[0095] Figure 8 The catalytic ozonation decomposition activity of the manganese cobalt spinel catalyst prepared in Example 1 on ethyl acetate was tested. The test conditions were: the test gas was ethyl acetate, the total gas flow rate was controlled to be 50 mL / min, the oxygen flow rate was 30 mL / min, the ozone concentration was 700 ppm, the N2 balance gas flow rate was 10 mL / min, the ethyl acetate concentration was 100 ppm (the original ethyl acetate concentration in the gas cylinder was 500 ppm), and the volume space velocity was 2400 h -1 The concentration of ethyl acetate in the tail gas was detected and analyzed by gas chromatography, and the concentration of ozone was detected by an ozone detector. Figure 8 It can be seen from the catalyst activity curve that the catalyst exhibits 100% catalytic ozonation activity of ethyl acetate at 53°C.
[0096] Application Example 7
[0097] Fig. 9The catalytic ozonation decomposition activity of the manganese-cobalt spinel catalyst prepared in Example 1 on methane was tested. The test conditions were: the test gas was methane, the total gas flow rate was controlled to be 100 mL / min, the oxygen flow rate was 30 mL / min, the ozone concentration was 700 ppm, the N2 balance gas flow rate was 50 mL / min, the methane concentration was 100 ppm (the original methane concentration in the gas cylinder was 500 ppm), and the volume space velocity was 2400 h -1 The methane concentration in the tail gas is detected and analyzed by gas chromatography, and the ozone concentration is detected by an ozone detector. Fig. 9 The catalyst activity curve shows that the catalyst can exhibit 100% catalytic ozonation activity for methane at 400°C.
[0098] Application Example 8
[0099] Fig.10 The catalytic ozonation decomposition activity of the manganese cobalt spinel catalyst prepared in Example 1 on the mixed gas was tested. The test conditions were: the test gas was 40 ppm toluene, 30 ppm ethyl acetate, 30 ppm xylene, the total gas flow rate was controlled to 100 mL / min, the oxygen flow rate was 30 mL / min, the ozone concentration was 700 ppm, the N2 balance gas flow rate was 33.7 mL / min, and the volume space velocity was 2400 h -1 The concentration of VOCs in the exhaust gas is detected and analyzed by gas chromatography, and the concentration of ozone is detected by an ozone detector. Fig.10 The catalyst activity curve shows that the catalyst can show 100% catalytic ozonation activity for xylene in the mixed gas and maintain it for 13 hours without decreasing. The degradation of toluene can be maintained at 100% within 14 hours. The degradation of ethyl acetate can be maintained at 100% within 16 hours. The test results show good room temperature catalytic ozonation decomposition activity for mixed components.
[0100] Application Example 9
[0101] Fig.11 The decomposition activity of the manganese-cobalt spinel catalyst prepared in Example 1 for ozone at room temperature and different humidity was tested. The test conditions were: test gas 17 ppm ozone, total flow rate 1.2 L / min, space velocity 18950 h -1 , air balance gas, test temperature is 25℃, ozone concentration in tail gas is detected by ozone detector. Fig.11It can be seen from the catalyst activity curve that the catalyst can achieve more than 85% ozone removal at room temperature when the humidity is 1% and can maintain basically unchanged for 13 hours, which shows that the catalyst has a good removal rate under dry gas conditions. At a humidity of 25%, it can achieve more than 81% ozone removal at room temperature and can maintain basically unchanged for 6 hours. At a humidity of 50%, it can achieve more than 71% ozone removal at room temperature and can maintain basically unchanged for 6 hours. At a humidity of 75%, it can achieve more than 55% ozone removal at room temperature and can maintain basically unchanged for 6 hours. This shows that the catalyst still has a certain removal rate for ozone under different humidity conditions.
[0102] Application Example 10
[0103] Fig.12 The commercial manganese oxide and manganese dioxide catalysts in Comparative Example 5 were tested for their room temperature catalytic ozonation decomposition activity on toluene. The test conditions were as follows: the test gas was 100 ppm toluene, the total gas flow rate was controlled to be 100 mL / min, the oxygen flow rate was 30 mL / min, the ozone concentration was 700 ppm, the N2 balance gas flow rate was 33.7 mL / min, and the volume space velocity was 2400 h -1 The concentration of VOCs in the exhaust gas is detected and analyzed by gas chromatography, and the concentration of ozone is detected by an ozone detector. Fig.12 The catalyst activity curve shows that the commercial manganese oxide (MnO) catalyst has a catalytic decomposition activity of 0% for toluene after 4 hours; in addition, the degradation of toluene by the commercial manganese dioxide (MnO2) catalyst drops to less than 10% after 24 hours. The test results show that the manganese cobalt spinel monolithic catalyst has a better room temperature catalytic ozonation decomposition activity than the single manganese oxide (MnO or MnO2) catalyst.
[0104] The above are only preferred specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A method for preparing a manganese-cobalt spinel catalyst, characterized in that: The following steps are involved: 1) adding manganese salt and cobalt salt into water and dissolving them by ultrasonic, immersing the honeycomb ceramic substrate in the obtained solution, and taking out the treated honeycomb ceramic substrate after the solution turns into light purple; Repeat dipping; 2) drying and calcining the honeycomb ceramic substrate after the impregnation treatment; 3) The calcined honeycomb ceramic substrate is immersed in an acetic acid solution, and then the excess solution in the pores is blown away, and then immersed in a lanthanum salt solution, and then the excess solution in the pores is blown away after being taken out, and then dried, and the temperature is raised and calcined again to obtain a manganese cobalt spinel catalyst.
2. The method for preparing the manganese-cobalt spinel catalyst according to claim 1, characterized in that: The repeated impregnation means that each time the manganese salt and the cobalt salt are added into water and ultrasonically dissolved to prepare a solution, and then the honeycomb ceramic substrate treated by the last impregnation treatment is placed into a new solution for a new round of impregnation treatment, and this complete process is repeated three times.
3. The method for preparing the manganese-cobalt spinel catalyst according to claim 1, characterized in that: In step 1), the parameters of the immersion are: temperature 85-95° C., time 4-4.5 hours.
4. The method for preparing the manganese-cobalt spinel catalyst according to claim 1, characterized in that: In step 1), the molar ratio of the manganese salt to the cobalt salt is 7:
10.
5. The method for preparing the manganese-cobalt spinel catalyst according to claim 1, characterized in that: The manganese salt is potassium permanganate, the cobalt salt is cobalt nitrate hexahydrate, and the lanthanum salt is lanthanum nitrate hexahydrate.
6. The method for preparing the manganese-cobalt spinel catalyst according to claim 1, characterized in that: In step 2) and step 3), The drying parameters are: temperature 150°C, time 6 hours; and / or The calcination parameters are: temperature 500° C., time 2.5 hours, heating rate 10° C. / min.
7. The method for preparing the manganese-cobalt spinel catalyst according to claim 1, characterized in that: In step 3), The concentration of the acetic acid solution is 0.1-0.2 mol / L; and / or The soaking parameters are: time 1-2 hours; and / or The concentration of the lanthanum salt solution is 0.15-0.2 mol / L; and / or The parameters of the immersion are: time 10-20 minutes.
8. A manganese-cobalt spinel catalyst prepared by the preparation method according to any one of claims 1 to 7.
9. Use of the manganese-cobalt spinel catalyst as claimed in claim 8 in catalytic ozonation of VOCs.
Citation Information
Patent Citations
Catalyst for purifying volatile organic pollutant and ozone in air under normal temperature as well as preparation and use thereof
CN101298024A
Catalyst for degrading ozone and removing VOCs synergistically as well as preparation method and application of catalyst
CN104084192A
Preparation method of composite non-precious metal oxide catalytic combustion catalyst and application of prepared catalyst
CN108889307A
Monolithic catalyst with metal oxide skeleton as well as preparation method and application of monolithic catalyst
CN116651433A
Monolithic catalyst for catalytic oxidation of VOCs (Volatile Organic Compounds) as well as preparation method and application of monolithic catalyst
CN118179529A
Cited By
Monolithic electric conduction and heat conduction manganese oxide catalyst as well as preparation method and application thereof
CN118892823A